L’interpretazione dei sogni nell’Islam. Un’introduzione - De Simone, Gianfranco; Fagioli, Luca (Il sogno della farfalla, 2007)
On the basis of a more attentive analysis of sources and critical texts available, the article looks into the elements which have characterized the attitude of the three revealed religions, especially Islam, towards the interpretation of dreams and the divinatory and magic irrational in the passage from polytheism to the one God. Whilst in Christianity divinatory powers are banned and the interpreters of dreams are condemned to death without exception, in the Old Testament only the elects of God are allowed to give interpretations. In Islam all magic and divinatory practices are disparaged and greater value attributed to dreams and the art of interpretation. Mohamed is the first interpreter of dreams which he uses to begin his prophesy. Through the ru’ya¯, lifelike dreams and the prophetic visions, the one God sends messages to the prophet and to the men of faith. Dreams and the research into images form a basis in the process of initiation of the Sufi, the mystics of Islam who use these means to realize the higher self which can, when abandoning itself to God, reach either levels of folly or exceptional forms of life and art.